2022
DOI: 10.3390/ijerph191912599
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the COVID-19 Pandemic on Physical Function of Community-Dwelling People with Disabilities in Japan

Abstract: In 2020, COVID-19 spread throughout the world, and international measures such as travel bans, quarantines, and increased social distancing were implemented. In Japan, the number of infected people increased, and a state of emergency was declared from 16 April to 25 May 2020. Such a change in physical activity could lead to a decline in physical function in people with disabilities. A retrospective study was conducted to determine the impact of the pandemic on the physical function of disabled persons living i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…Previous studies have reported that lower extremity muscle strength is associated with exercise tolerance and prognosis in patients with cardiac disease (Hülsmann et al, 2004; Izawa et al, 2012; Thomaes et al, 2012). In addition, a previous study in older adults reported a decrease in lower extremity function, such as walking speed, before and after the emergency declaration (Kamimoto et al, 2022). Their behavioural restrictions associated with exposure to the emergency declaration may have resulted in a decline in lower extremity muscle strength and oxygen availability, causing a significant decline in exercise tolerance.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have reported that lower extremity muscle strength is associated with exercise tolerance and prognosis in patients with cardiac disease (Hülsmann et al, 2004; Izawa et al, 2012; Thomaes et al, 2012). In addition, a previous study in older adults reported a decrease in lower extremity function, such as walking speed, before and after the emergency declaration (Kamimoto et al, 2022). Their behavioural restrictions associated with exposure to the emergency declaration may have resulted in a decline in lower extremity muscle strength and oxygen availability, causing a significant decline in exercise tolerance.…”
Section: Discussionmentioning
confidence: 93%
“…The smaller amount of exercise during the pandemic significantly reduced EF, and even people with previously healthy cognitive function may have experienced cognitive function decline due to reduced activity [19]. In a previous study that measured TUG scores before and after the pandemic, people with a walking speed of 1.0 m/s or lower before the pandemic had a significant reduction in TUG scores [20], suggesting that people with a slow walking speed are at high risk of functional decline. Restoration of walking function in elderly people is an important priority post-pandemic and the restoration of gait demonstrated in this study should be seen as an opportunity to further distribute and expand this initiative to restore functionality and maintain restored function.…”
Section: Discussionmentioning
confidence: 96%